1977
DOI: 10.1021/bi00632a031
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comparative aspects of the serum very low and low density lipoproteins and their apoproteins in the chicken (Gallus domesticus)

Abstract: Sera from young laying chickens, found to be hypertriglyceridemic by serum lipid and lipoprotein analyses, were fractionated by ultracentrifugation into very low ( d < 1.006 g/mL) and low density ( d 1.006-1.063 and 1.024-1.045 g/mL) lipoproteins (VLDL and LDL). The purity of these lipoprotein fractions was evaluated by electrophoretic, immunological, and electron microscopic techniques; their chemical and physical properties were subsequently determined and compared with those of the corresponding human fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
22
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 43 publications
(83 reference statements)
6
22
0
Order By: Relevance
“…Thus the complement of non-apo-B apoproteins in laying hen VLDL appeared less complex than in the immature chicken [13], in accordance with previous studies demonstrating the absence of certain apolipoproteins from chicken VLDL after estrogen treatment [8]. Nonetheless, other investigators [7] have described the occurrence of numerous protein species in laying hen VLDL, which could be attributable to proteolytic products of apo B-100 [39, 401 (see above).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Thus the complement of non-apo-B apoproteins in laying hen VLDL appeared less complex than in the immature chicken [13], in accordance with previous studies demonstrating the absence of certain apolipoproteins from chicken VLDL after estrogen treatment [8]. Nonetheless, other investigators [7] have described the occurrence of numerous protein species in laying hen VLDL, which could be attributable to proteolytic products of apo B-100 [39, 401 (see above).…”
Section: Discussionsupporting
confidence: 88%
“…5). Indeed earlier studies in our laboratory, using analytical ultracentrifugation, suggested that concentrations of Sr 0-12 LDL were below 50 mg/dl in laying hens [7], a finding confirmed upon column chromatographic separation of laying hen LDL [9]. Conversely, some authors have described an increase in LDL levels upon isolation by sequential ultracentrifugation within the density range 1.006 -1.063 g/ml [X, 3611.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Several immunological studies of the serum low-density lipoprotein (LDL) from both mammalian and non-mammalian species have indicated that the antigenic structure(s) of LDL has been relatively highly conserved during evolution [6,7]; however, only a few comparative immunological studies of serum HDL have been described. Thus dog [8], chicken [9], and marmoset [10] apo Al gave a pattern of partial identity with the human protein.…”
Section: Introductionmentioning
confidence: 99%